Pathways of power : building an anthropology of the modern world - Wolf, Eric R., 1923-1999 (University of California Press, 2001)
This collection of 28 essays by renowned anthropologist Eric R. Wolf is a legacy of some of his most original work, with an insightful foreword by Aram Yengoyan. Of the essays, six have never been published and two have not appeared in English until now.